Assessment of risk factors in patients undergoing difficult cholecystectomy: a cross-sectional study at a tertiary care hospital in Central India - Chandak, Unmed; Chauhan, Kapil; Gupta, B. B.; Mitra, Arti; Bansod, Prasad; Upadrashta, Rohit; Mundhada, Aditi (International Surgery Journal, 2023)
Background: Laparoscopic cholecystectomy (LC) is the operation of choice in the treatment of symptomatic gallstone disease. Most of the time, the levels of difficulties are hard to assume. The risk factors for difficult LC have not been adequately evaluated in Indian population, especially with respect to western Indian population. Thus, the present study was undertaken to assess the risk factors in patients undergoing difficult cholecystectomy. Method: The study involved 100 adult patients with cholelithiasis admitted in the department of surgery for cholecystectomy over a period of 2 years from Nov 2020 to Dec 2022. Preoperatively, patients were evaluated for risk factors including age, gender, BMI, history of sickle cell disease, previous abdominal surgery, presence of pericholecystic collection, gall bladder thickness, impacted calculi, adhesions in triangle of Calot‘s, and previous hospitalization for acute cholecystitis and acute pancreatitis. These factors were assessed to predict difficult LC. Results: Majority of laparoscopic procedures were easy (65%), while remaining were difficult (35%). Difficult cholecystectomy was significantly associated with age ≥50 years (p=0.016), male gender (p=0.031), BMI ≥25 kg/m2 (p<0.0001), sickle cell disease (p=0.030), previous abdominal surgery (p=0.004), pericholecystic collection (p=0.017), gall bladder thickness ≥4 mm (p=0.007), adhesion in triangle of Calot‘s (p<0.0001), impacted calculi (p=0.036), previous hospitalization for acute cholecystitis and acute pancreatitis (p<0.0001) and diabetes mellitus (p<0.0001). The conversion rate was 2%. Conclusions: An awareness about reliable predictors for difficult LC would be helpful for an appropriate treatment plan and application of the resources to anticipate difficult LC. However, further studies with larger sample size are required to confirm the findings.